بلوچی نبشتہ راہبند ءِ سرا سرکاری ءُ درسرکاری سیمینار ءُ مراگش (بُندپتری پژدر ءَ پولکاری وانشت): Official and Non-Official Seminars on Balochi Script (Background and Analytical Studies) - Meer, Muhammad Sarif (Hanken, 2020)
A seminar may have a single or several purposes such as; a seminar may be for the purpose of special education, female education, early childhood education or on mother tongue education, where the academicians, researcher or scholars engaged with the discussion on a subject with the aim of ontaining or gaining a better insight into the subject matter. When we look at a glance in the history of the Balochi Language and Literature, we come to conclude that different seminars have been conducted in different times for the standardization of the Balochi orthography, but the scholars and academicians did not come to a final conclusion or did not finalize a single orthography for the Balochi Language. This Paper illustrates the historical Background of the seminars which were conducted for the purpose of the standardization of the Balochi orthography.